Feature flag best practices : advanced tips for product delivery teams - Hodgson, Pete; Echagüe, Patricio (O'Reilly Media, 2019)
Whether you want to fine-tune operational control or conduct A/B/n tests, feature flags make it easy to deliver software features quickly and safely. With this practical book, software engineers will learn eight best practices for using feature flags in production, including how to configure and manage a growing set of feature flags within your product, maintain them over time, manage infrastructure migrations, and more. Pete Hodgson and Patricio Echag|e demonstrate how feature flags help modern product delivery teams reduce risk by decoupling code deployment from feature release. You'll learn how to maintain flag consistency in different scenarios and how to develop, test, and work with feature flags at scale. With these practices, you will: Make sure users in a test still have access once a feature is ramped up Learn flag strategies for transitioning users from "anonymous" to "logged in" Keep flagging decisions on the server to maintain performance and security Use patterns to make incremental, backward-compatible database changes Implement flagging decisions as close to business logic as possible Have each flag owned by one team responsible for rollout and monitoring Consider testability when using feature flags in combination with CI practices Maintain a process for identifying and tracking flags Examine the effect a feature flag is having on your business